2015
DOI: 10.1590/2317-1782/20152015043
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de linguagem e funções cognitivas em crianças com dislexia falantes do Português Brasileiro

Abstract: Phonological abilities demonstrated to be the main difficulty observed in children with dyslexia investigated in this study, corroborating previous studies in other languages. This demonstrates that, independently of the language regularity, phonological skills are fundamental to the diagnosis of developmental dyslexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
0
4
0
9
Order By: Relevance
“…Reinforcing this hypothesis, another international study (18) , carried out in the United States, presented a comparison of the degree of performance in two cognitive skills, phonological awareness and processing speed, in two groups of different age groups of dyslexic children, to evaluate processing speed and phonological awareness with their performance in component reading skills and determine which of these two cognitive constructs served as stronger simultaneous predictors of separate component reading skills. As in the Brazilian study (30) and the two Europeans (32,40) , it was observed that younger children showed greater losses in processing speed tasks when compared to phonological awareness tasks.…”
Section: Analysis Of Selected Studiesmentioning
confidence: 54%
See 2 more Smart Citations
“…Reinforcing this hypothesis, another international study (18) , carried out in the United States, presented a comparison of the degree of performance in two cognitive skills, phonological awareness and processing speed, in two groups of different age groups of dyslexic children, to evaluate processing speed and phonological awareness with their performance in component reading skills and determine which of these two cognitive constructs served as stronger simultaneous predictors of separate component reading skills. As in the Brazilian study (30) and the two Europeans (32,40) , it was observed that younger children showed greater losses in processing speed tasks when compared to phonological awareness tasks.…”
Section: Analysis Of Selected Studiesmentioning
confidence: 54%
“…Thus, changes in categorical speech perception at the behavioral level would not be directly associated with dyslexia. Other three studies, one national (30) and two with Portuguese children (32,40) , all in the age group between 7 and 14 years old, verified the presence of specific changes in the phonological processing of children and adolescents with dyslexia and its association with the fluency of reading and reading accuracy, further investigating the diagnostic accuracy of phonological processing measures to correctly discriminate between typical readers and dyslexic children. There were significant differences between groups, in which all tasks with dyslexic subjects performed less than that of the control group.…”
Section: Analysis Of Selected Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…All the children were submitted to a broad neuropsychological battery comprising tests and tasks involving oral language, reading and writing, in individual sessions of approximately one hour each. The dyslexia diagnosis was based on the following instruments: CONFIAS -the Phonological Awareness, Instrument of Sequential Assessment; the TDE School Performance Test; reading and writing of words and pseudowords; reading silently and reading aloud task; and a reading comprehension task (see Cruz-Rodrigues et al 19 and Barbosa et al 24 for further explanations about these tests).…”
Section: Participantsmentioning
confidence: 99%
“…Por isso, há a dificuldade da criança e de adultos disléxicos, principalmente os que não foram devidamente ensinados, em reconhecer palavras, decodificá-las e escrevê-las. Línguas com baixa relação letra-som (como o inglês) apresentam dificuldades muito maiores para aquisição por indivíduos disléxicos do que línguas com alta relação letra-som, como o finlandês (Capellini, Germano, & Cardoso, 2008;Barbosa, Rodrigues, Toledo-Piza, Navas, & Bueno, 2015;Silva & Capellini, 2015;Matta, Perrut, & Alcântara, 2017;Luca & Nico, 2018).…”
Section: [Grifo Nosso] (Pei)" (P 19)unclassified